Models for Practical Routing Problems in Logistics Design and Practices - Anbuudayasankar, S. P.; Ganesh, K.; Mohapatra, Sanjay; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book deals with complex variants of Travelling Salesman Problem (TSP) and Vehicle Routing Problem (VRP) within the manufacturing and service industries. The objective is to develop heuristics for these supply chain problems in order to offer practical solutions to improve operational efficiency. These heuristics are evaluated using benchmark and derived data-sets. Case studies pertaining to logistics in different industries including textile machinery manufacturing and banking are also included to demonstrate the created heuristics. High competition in today$1 (Bs global market has forced the organizations to invest in and focus on their logistics system. The critical function of logistics is the transportation within and across various supply chain entities. Both supply and distribution procedure require effective transportation management. A small improvement in routing problems can lead to huge logistics savings in absolute terms. This book should appeal to executives, researchers and consultants seeking supply chain management solutions.s
Introduction -- Survey of Methodologies for TSP and VRP -- Routing for Balanced Logistics -- Routing for Reverse Logistics -- Routing for Distribution Logistics -- Routing for Urgency Logistics -- Conclusions.
Keywords: Economics; Operations research; Economics/Management Science; Production/Logistics/Supply Chain Management; Transportation; Operation Research/Decision Theory